2007
DOI: 10.1021/es063062j
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Migration of Steroidal Estrogens through River Bed Sediments

Abstract: Estrogenic substances discharged from wastewater treatment plants have been detected in surface sediments of receiving waters, but little is known of their vertical migration through buried sediments and their potential to contaminate subsurface waters. The vertical profiles of estrogenic chemicals were investigated in sediment cores at an alluvial freshwater site (Ditchling) and a clay-rich estuarine site (Lewes), both of which are downstream of wastewater discharges into the River Ouse (Sussex, U.K.). Estron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 29 publications
(52 reference statements)
3
30
0
1
Order By: Relevance
“…They may also pose a potential environmental threat to aquatic organisms. Owing to the importance of sediments on the transport, fate and bioavailability of EDCs, investigations on the sediment contamination of EDCs have been widely carried out (Naylor et al, 1992;Hale et al, 2000;Isobe et al, 2001;Heemken et al, 2001;López de Alda et al, 2002;Jonkers et al, 2003;Rice et al, 2003;Li et al, 2004a,b;Patrolecco et al, 2004;Chen et al, 2006;Fu et al, 2007;Labadie et al, 2007), and phenolic xenoestrogens with high levels were reported worldwide. For example, the sedimentary concentrations of nonylphenol and octylphenol were up to 72,000 ng/g and 1800 ng/ g dw, respectively, from Hamilton Harbor of the Great Lakes, Canada, which was highly impacted by anthropogenic activities (Bennie et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…They may also pose a potential environmental threat to aquatic organisms. Owing to the importance of sediments on the transport, fate and bioavailability of EDCs, investigations on the sediment contamination of EDCs have been widely carried out (Naylor et al, 1992;Hale et al, 2000;Isobe et al, 2001;Heemken et al, 2001;López de Alda et al, 2002;Jonkers et al, 2003;Rice et al, 2003;Li et al, 2004a,b;Patrolecco et al, 2004;Chen et al, 2006;Fu et al, 2007;Labadie et al, 2007), and phenolic xenoestrogens with high levels were reported worldwide. For example, the sedimentary concentrations of nonylphenol and octylphenol were up to 72,000 ng/g and 1800 ng/ g dw, respectively, from Hamilton Harbor of the Great Lakes, Canada, which was highly impacted by anthropogenic activities (Bennie et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogens, both E1 and E2, have been observed in sediments at concentrations of up to 20 -30 ng g -1 , and at depths relating to over 100 years of sedimentation, although migration was attributed to their presence at depth at this location (Labadie et al 2007). In the core from Tilbury, accumulation was relatively rapid, and the presence of contaminants is deemed to reflect historic inputs.…”
Section: Discussionmentioning
confidence: 93%
“…Microwave-assisted solvent extraction (MASE) was used for manure and soil samples (Camel, 2000;Labadie et al, 2007) and is described in detail elsewhere (Snow et al, 2013). Briefly, 2 to 3 g of sample were weighed into a 10 mL Teflon microwave digestion vessel and mixed with 1 mg of butylated hydroxytoluene and 5 mL of high-purity methanol (Labadie et al, 2007;Matejicek et al, 2007), 25 ng of internal standards (testosterone-d 3 and 13 C 6 -estradiol) and 17α-methyltestosterone (used as a surrogate compound to monitor recovery) was added by pipette, and the contents were vortexed prior to microwaving (MARS Xpress, CEM Corp., Matthews, N.C.) at 1000 W for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 2 to 3 g of sample were weighed into a 10 mL Teflon microwave digestion vessel and mixed with 1 mg of butylated hydroxytoluene and 5 mL of high-purity methanol (Labadie et al, 2007;Matejicek et al, 2007), 25 ng of internal standards (testosterone-d 3 and 13 C 6 -estradiol) and 17α-methyltestosterone (used as a surrogate compound to monitor recovery) was added by pipette, and the contents were vortexed prior to microwaving (MARS Xpress, CEM Corp., Matthews, N.C.) at 1000 W for 10 min. Surrogate (17α-methyltestosterone) recovery averaged 97% ±23% over all solid samples.…”
Section: Methodsmentioning
confidence: 99%